The Human Resources Information System and Information Technologies Requirement Case study: a sample of Algerian telecom agencies - Boudiaf, Ilyes; Belhadj, Tarek (Finance and Business Economies Review, 2019)
We aim through this study mainly to measure the correlation between information technology and human resources information system through its dimensions. For that we have put a model that shows the relationship between the variables studied (information technology and human resources information system). This study has been conducted on a sample of 32 agencies of the Algerian east area, depending on survey method and discipline to collect and analyze the data by a set of statistical indicators such Cronbach's Alpha, One-Sample Kolmogorov-Smirnov Test, descriptive statistics such (Mean, Std. Deviation, Std. Error Mean) and correlation coefficient for testing the hypotheses, with SPSS V20. The main result of this study is: there is a positive- high correlation between information technology dimensions and developing the performance of human resources information system.